STUDENT FRIENDLY IN ISLAMIC BOARDING SCHOOL (Analytical Study at the Mualimaat Muhammadiyah Yogyakarta Islamic Boarding School) - uswatun hasanah (Edusoshum : Journal of Islamic Education and Social Humanities, 2023)
Islamic boarding schools are the oldest form of indigenous institution in Indonesia, even older than the Republic of Indonesia. Until now the pesantren system is still used as an educational institution to shape character which is considered very effective because Islamic boarding schools as educational institutions are expected not only to give birth to generations who are intellectually intelligent but also capable and intelligent emotionally and spiritually. This study aims to answer how education in the Muallimaat Islamic boarding school is a santri-friendly boarding school from the perspective of K.H Ahmad Dahlan's thought. In this study, the authors used a qualitative research type method field research. In collecting data, researchers took primary data sources in this study by observing the condition of Islamic boarding schools and interviewing informants with related parties. And secondary data were obtained from the pesantren's guided book, the official website of the pesantren, and supporting journals. Data analysis techniques were carried out through the observation stage in the Islamic boarding school environment, interviews with 10 informants including the Director IV of the Islamic Boarding School section, teachers or ustadzah, Counseling Guidance (BK) and students randomly and documentation. Data analysis was obtained through the stages of data reduction, data presentation, and drawing conclusions. Data validation technique using source triangulation. Based on the results of the analysis, the results of this study show that the Muallimaat Islamic Boarding School has been categorized as a santri-friendly Islamic boarding school from the perspective of K.H Ahmad Dahlan, Muallimaat is a modern pesantren model by integrating the curriculum of the Ministry of Education and Culture, Ministry of Religion, and Muhammadiyah Curriculum. Through the pesantren program provided for students with the support of stakeholders, they are able to create a student-friendly boarding school environment. By learning to read situations and conditions that continue to change according to the times, it is mandatory for educational institutions, teaching staff and students to continue to upgrade and evaluate themselves, be open-minded and forward. Less educational into a system that promotes basyiran (good news) and tanzir (warnings) that educate or positive discipline.